Elongated styloid process evaluation on digital panoramic radiographs: A retrospective study - MunBhawni Bagga; Deepankar Bhatnagar; Nishant Kumar (Wolters Kluwer Medknow Publications, 2020)
Background: The precise knowledge about anatomy of both normal and abnormal styloid process is important for clinicians, surgeons, and radiologists. Thus, the present study highlighted the prevalence of anatomic-radiological features of elongated Styloid process on panoramic radiography. Aim: The aim of the study was to evaluate and classify the radiographic appearance of the Styloid process (SP) along with morphologic characteristics and patterns of calcification according to the subject gender and site predilection. Materials and Method: A random sample of 1706 good quality digital panoramic radiographs were included in present study. Elongated SPs were classified with the radiographic appearance based on morphology and calcification pattern. The data were analyzed by using student t test and Chi-squared with significance set at P = 0.05. Results: Bilateral elongation having "Elongated" Type SP with "partially calcified" pattern was the most frequent SP. No correlation was found between SP type and calcification pattern and subject gender, although elongated Styloid was more prevalent among male population (P < 0.001). Conclusion: Dentists should recognize the existence of morphological variation in elongated Styloid process apparent on panoramic radiographs. According to our knowledge, this is the first study conducted in Solan region to evaluate Styloid process elongation (SPE) and also had recorded highest prevalence of SPE in comparison with other studies conducted in Indian population. We found calcification of the Styloid process is common in older age groups with no correlation to gender and site predilection. "Type I" with "partially calcified" of the Styloid process was observed most frequently in the population studied.